2005
DOI: 10.1182/blood-2004-11-4502
|View full text |Cite
|
Sign up to set email alerts
|

In vitro functional analysis of human ferroportin (FPN) and hemochromatosis-associated FPN mutations

Abstract: Type IV hemochromatosis is associated with dominant mutations in the SLC40A1 gene encoding ferroportin (FPN). Known as the "ferroportin disease," this condition is typically characterized by high serum ferritin, reduced transferrin saturation, and macrophage iron loading. Previously FPN expression in vitro has been shown to cause iron deficiency in human cell lines and mediate iron export from Xenopus oocytes. We confirm these findings by showing that expression of human FPN in a human cell line results in an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
176
1
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(195 citation statements)
references
References 35 publications
10
176
1
1
Order By: Relevance
“…This lack of evidence for HFE4 is somewhat unexpected, as heterozygous loss-offunction SLC40A1 mutations have previously been associated with HFE4. 41,42 However, as the age of onset of HFE4 is up to 60 years in males and B10 years later in females (age-related penetrance), 43 it is possible that young carriers of the SLC40A1 deletion failed to present clinical symptoms of HFE4 in this study because of their age of 15 (53I, female), 18 (53J, male), and 49 (53E, male) years at examination. As, to our knowledge, no patient with complete hemizygous deletion of this gene has previously been reported at the molecular level, this is the first description of the (so far normal) clinical phenotype of individuals with true SLC40A1 haploinsufficiency, suggesting the negligible role of haploinsufficiency in the pathogenesis of HFE4.…”
Section: Discussionmentioning
confidence: 62%
“…This lack of evidence for HFE4 is somewhat unexpected, as heterozygous loss-offunction SLC40A1 mutations have previously been associated with HFE4. 41,42 However, as the age of onset of HFE4 is up to 60 years in males and B10 years later in females (age-related penetrance), 43 it is possible that young carriers of the SLC40A1 deletion failed to present clinical symptoms of HFE4 in this study because of their age of 15 (53I, female), 18 (53J, male), and 49 (53E, male) years at examination. As, to our knowledge, no patient with complete hemizygous deletion of this gene has previously been reported at the molecular level, this is the first description of the (so far normal) clinical phenotype of individuals with true SLC40A1 haploinsufficiency, suggesting the negligible role of haploinsufficiency in the pathogenesis of HFE4.…”
Section: Discussionmentioning
confidence: 62%
“…24 It has been reported for the main V162del mutation and to a lesser extent for the older A77D mutation, which has been associated with an age-dependent rise in transferrin saturation. These loss-of-function mutations do not impede the action of wild-type ferroportin in vitro 115 and may cause the disease by haploinsufficiency, a model consistent with the autosomal dominant trait of the disease and first suggested by Montosi et al 106 The model is related to a more pronounced effect of the mutation considered on iron recycling from senescent erythrocytes by macrophages, which normally supply B20 -30 mg of iron per day, than on absorption of dietary iron by enterocytes, which normally supply B1 mg of iron per day. 122 In that case, iron retention by macrophages leads to accumulation of iron in the tissue, which explains the high-serum ferritin levels, and reduces the serum iron available for erythropoiesis, which explains the low transferrin saturation.…”
Section: Molecular Genetics Of Haemochromatosismentioning
confidence: 99%
“…Further investigations may help to explain this phenotypic heterogeneity, in particular the search for modifier factors, but the very recent studies of Schimanski et al 115 have supplied some very important information. These authors first showed that the 77D, V162del and 490D ferroportin protein displayed a greatly reduced capacity to reach the Figure 5 Schematic representation of mutations in the SCL40A1 gene.…”
Section: Molecular Basismentioning
confidence: 99%
“…In patients with type A disease, SLC40A1 mutations generate a protein that is defective in cell surface expression or loss of iron export function. 42,43,44 In the less prevalent type B, the mutant gene generates proteins that show normal cell surface expression but reduced sensitivity to hepcidin. 42,43 The resistance of ferroportin to hepcidin might be the key not only to the iron overload of ferroportin disease, but also to the secondary iron overload syndromes.…”
mentioning
confidence: 99%